Nutrient Utilisation, Growth Performance and Blood Parameters in Weaned Piglets Fed Different Levels of Sun-dried Bovine Rumen Contents - Gebrehawariat, Efrem; Animut, Getachew; Urge, Mengistu; Mekasha, Yoseph (Indian Journal of Animal Nutrition, 2017)
This study was conducted to examine the effect of feeding different proportions of sun- dried bovine rumen contents (SDRC) on intake, digestibility, growth and haematology of weaned piglets. A total of 20weaned Yorkshire piglets (~7 weeks; 12.15±4.66 kg BW) were divided into 4 groups of 5 animals each using complete randomized design. The SDRC was included at 0, 5, 10 and 15% levels in treatments T1, T2, T3 and T4, respectively. The intakes of DM, CP and NDF were similar in all the treatments. The average ADF intake was higher (P